Pengaruh Modifikasi Pipa Masukan Bahan Bakar Oli Bekas Berbentuk Spiral Terhadap Performansi Burner Tornado Api - Gafur, abdul (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2020)
The need for fuel in Indonesia is a serious problem in human life in the future. Various efforts are being made to find alternative fuels. One that is currently being researched as an alternative fuel is lubricating oil (oil). Several studies have been carried out in the context of developing this used fuel oil. Used oil when using the standard burner used in previous studies has an impact on the amount of smoke and low temperature, because the oil that goes to the burner is still pure oil. This research tries to modify the oil input flow in the form of a circular spiral. The difference between the burners that will be made with previous studies is in the oil intake hose. The oil inlet pipe in this study will be made in a spiral shape. The results showed that the modification using a spiral pipe had a higher temperature of 397 0C compared to without using a spiral pipe which was 381 0C. In addition, the heating rate using this spiral pipe is greater, namely 302400 Joules. So it can be concluded that the burner performance with spiral pipe modification is higher than without using spiral pipe